Simple Resistor-less Generator Utilizing Z-copy Controlled Gain Voltage Differencing Current Conveyor for PWM Generation - Jerabek, Jan; Sotner, Roman; Dostal, Tomas; Vrba, Kamil (Elektronika ir Elektrotechnika, 2015)
This paper deals with a very simple functional generator employing single multi-terminal advanced active device, so-called z-copy controlled gain voltage differencing current conveyor (ZC-CG-VDCC). This active element offers various inter-terminal relations and interesting possibilities of multi-parameter electronic control, which are utilized to control resulting application (triangular and square wave generator). Simple pulse width modulator (PWM) based on two ZC-CG-VDCCs is a further application example of presented generator. Verification of expected behavior was performed by simulation based on CMOS model of the ZC-CG-VDCC and also by lab measurement.DOI: http://dx.doi.org/10.5755/j01.eee.21.5.13322